MINAT SISWA SMKN 1 KEDAWUNG CIREBON TERHADAP BAHASA, BUDAYA DAN KESEMPATAN BEKERJA DI JEPANG - Sundasewu, Rama Ulun; Amalia, Aan; Ranadireksa, Dinda Gayatri (Jurnal Abdimas Bina Bangsa, 2024)
This study discusses the interest of students at SMKN 1 Kedawung in the language, culture, and job opportunities in Japan. The purpose of this study is to understand the students' interest in the language, culture, and job opportunities in Japan. This research uses a descriptive method with a qualitative approach. The object of this study is the interest of students at SMKN 1 Kedawung in the language, culture, and job opportunities in Japan. The results of this study indicate that the interest of SMKN 1 Kedawung students in Japanese language and culture falls into the category of interested students, with a total of 28 student respondents. From a total of 5 questions and 28 student respondents, the interest calculation showed that 28 students (100%) were interested in learning the Japanese language, 26 students (96.4%) were interested in learning about Japanese culture, 28 students (100%) understood why Japan is an advanced country, 26 students (96.4%) were interested in the positive values of Japanese life, and 28 students (100%) were interested in going to Japan. Similarly, the interest of SMKN 1 Kedawung students in working in Japan is categorized as interested. From a total of 1 question and 28 student respondents, the interest calculation showed that 12 students (42.9%) strongly agreed, 13 students (46.4%) agreed, 3 students (10.7%) somewhat agreed, and no students disagreed